Interactive Teaching Media Design for Past Tense Lesson Material Using VB.NET - Syahputra, Fahmy; Putri, Tansa Trisna Astono; Lubis, Khodijah May Nuri; Rahmadhani, Alfi; Fattah, M (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
The development of information technology has influenced the use of various types of media, as a tool in the learning process. So teachers are expected to be able to use these tools or equipment effectively classroom learning. In this article, we design teaching media or applications for English subjects. This teaching media is designed using the Microsoft Visual Studio 2022/VB.Net programming language with Past Tense subject matter. The aim of this teaching media design is to increase students' understanding through a visual and interactive approach. This application provides a menu including simple past tense, past continuous tense, past perfect tense, past perfect continuous tense, and is equipped with quiz questions. With this, it is hoped that students will be more involved in the learning process so that they can master the use of past tense effectively and have fun.